Effects of educational technology in relation to the acquisition listening comprehension skill among preschool and kindergarten at Aguacatal Elementary School - Ríos Guerra, Vicky Itzel; Concepción García, Kevin Gabriel (David, Panamá : UDELAS, 2014)
The integration of technology in education is no longer a new idea because technology has become an essencial part of society. However, it is necessary to integrate its use in education in a variety of ways to help students to acquire english language in aan easy way.
TABLE OF CONTENTS TABLE INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTECEDENTS AND STATEMENT OF THE PROBLEM 1.1. Background 1.2. Statement of the problem 1.3. Objectives 1.3.1. General objectives 1.3.2. Specific objectives 1.4. Justificación CHAPTER II: THEORETICAL FRAMEWORK 2.1. Educational technoplogy 2.1.1. History 2.1.2. Nature of the educational technology 2.1.3. Meaning 2.1.4. Learning theories 2.2. Effects of educatibe technology 2.2.1. Increased motivation and self esteem 2.2.2. Engage the four key components in learning 2.2.3. Academic success 2.2.4. Change the role of teacher and students 2.3.Preschool and kindergarten characteristics 2.3.1. Characteristics 2.3.2. Physical characteristic 2.3.3. Social and emotional development 2.3.4. Cognitive stage 2.4. Mobile learning 2.4.1. Concept 2.4.2. The use of mobile learning devices 2.4.3. Mobile learning application 2.5. Listening comprehension 2.5.1. Concept 2.5.2. Importance of listening comprenhension 2.5.3. Listening comprehension process 2.5.4. The effect of technology on listening comprehension skills CAPTER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.1.1. Quantitative research 3.1.2. Exploratory research 3.2. Source of information 3.2.1. Material sources 3.2.2. Human sources 3.3. Variable system 3.3.1. Educational technology educational technology 3.3.1.1. Conceptual definition 3.3.1.2. Instrumental definition 3.3.1.3. Operational definition 3.3.2. Effects of educational technology 3.3.2.1. Conceptual definition 3.3.2.2. Instrumental definition 3.3.2.3. Operational definition 3.3.3. Preschool and kindergarten characteristic 3.3.3.1. Conceptual definition 3.3.3.2. Instrumental definition 3.3.3.3. Operational definition 3.3.4. Mobile learning and educational apps 3.3.4.1. Conceptual definition 3.3.4.2. Instrumental definition 3.3.4.3. Operational definition 3.3.5. Listening comprehension 3.3.5.1. Conceptual definition 3.3.5.2. Instrumental definition 3.3.5.3. Operationa definition CHAPTER IV: 4.1. Observations of technological effects applied to students al Aguacatal Elementary School 4.1.1. Variable: Educational technology 4.1.2. Variable: Effects of educational technology 4.1.3. Variable: Pre and kinder garden characteristics 4.1.4. Variable: Educationa apps 4.1.5. Variable: Listening comprehension 4.2. Analysis of the interview of preschool and kindergarten teacher in the Aguacatal Elementary School 4.2.1. Variable: Educational technology 4.2.2. Variable: Effect of educational technology 4.2.3. Variable: Characteristics of preschool and kindergarten 4.2.4. Variable: Mobile devices 4.2.5. Variable: Listening comprehension skills CONCLUSIONS RECOMENDATIONS BIBLIOGRAPHY
Incluye Table of contents
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio.
No se saca fotocopias.
Keywords: ENGLISH -- TESIS; INGLÉS -- TESIS; EDUCATIONAL TECHNOLOGY -- TESIS; LICENCIATURA EN DOCENCIA EN INGLÉS - TESIS; AGUACATAL ELEMENTARY SCHOOL